To simplify the given expression, let's first distribute the fractions:
1/2(x + 4) + 1/4(4x - 2)
= (1/2)x + (1/2)(4) + (1/4)4x - (1/4)2
Simplifying further:
= (1/2)x + 2/2 + (4/4)x - 2/4
= (1/2)x + 1 + (1)x - 1/2
Combining like terms:
= (1/2)x + (1)x + 1 - 1/2
= (3/2)x + 1/2
To write this answer in mixed number form, we divide the numerator (3) by the denominator (2):
3 รท 2 = 1 with a remainder of 1
So the answer is 1 1/2 in mixed number form.
Add 1/2 (x + 4) + 1/4(4x - 2). Answer should be in mixed number form
13 answers
Add 1/2 (x + 4) + 1/4 (4x - 2) In mixed number form.
To add the fractions, we need a common denominator. In this case, the common denominator is 4, since both fractions have denominators of 2 and 4.
1/2 (x + 4) + 1/4 (4x - 2) =
(2/4)(x + 4) + (1/4)(4x - 2)
Now, distribute the fractions:
(2/4)(x + 4) = (2/4)x + (2/4)(4) = (1/2)x + 2/4
(1/4)(4x - 2) = (1/4)(4x) - (1/4)(2) = x - 1/2
Now, add the given expressions:
(1/2)x + 2/4 + x - 1/2
Combine like terms:
(1/2 + 1)x + (2/4 - 1/2) =
(3/2)x + (4/4 - 2/4) =
(3/2)x + 2/4
The answer in mixed number form is:
1 1/2x + 1/2
1/2 (x + 4) + 1/4 (4x - 2) =
(2/4)(x + 4) + (1/4)(4x - 2)
Now, distribute the fractions:
(2/4)(x + 4) = (2/4)x + (2/4)(4) = (1/2)x + 2/4
(1/4)(4x - 2) = (1/4)(4x) - (1/4)(2) = x - 1/2
Now, add the given expressions:
(1/2)x + 2/4 + x - 1/2
Combine like terms:
(1/2 + 1)x + (2/4 - 1/2) =
(3/2)x + (4/4 - 2/4) =
(3/2)x + 2/4
The answer in mixed number form is:
1 1/2x + 1/2
Add: (4d - 3) + (12d + 4)
To add the given expressions, we simply combine like terms:
(4d - 3) + (12d + 4) = 4d + 12d - 3 + 4
Combining the variable terms and the constant terms:
= (4d + 12d) + (-3 + 4)
= 16d + 1
Therefore, the sum of (4d - 3) and (12d + 4) is 16d + 1.
(4d - 3) + (12d + 4) = 4d + 12d - 3 + 4
Combining the variable terms and the constant terms:
= (4d + 12d) + (-3 + 4)
= 16d + 1
Therefore, the sum of (4d - 3) and (12d + 4) is 16d + 1.
(2m - 3) + (3n - 1) + (3m + 1)
To add the given expressions, we need to combine like terms:
(2m - 3) + (3n - 1) + (3m + 1)
First, combine the "m" terms: 2m + 3m = 5m
Now, combine the constant terms: -3 - 1 + 1 = -3
Finally, the expression becomes:
5m + 3n - 3
Thus, the sum of (2m - 3) + (3n - 1) + (3m + 1) is 5m + 3n - 3.
(2m - 3) + (3n - 1) + (3m + 1)
First, combine the "m" terms: 2m + 3m = 5m
Now, combine the constant terms: -3 - 1 + 1 = -3
Finally, the expression becomes:
5m + 3n - 3
Thus, the sum of (2m - 3) + (3n - 1) + (3m + 1) is 5m + 3n - 3.
2(10b + 4) - (b - 2)
To simplify the given expression, let's first distribute the number 2:
2(10b + 4) - (b - 2) = 20b + 8 - (b - 2)
Next, distribute the negative sign inside the parentheses:
20b + 8 - b + 2
Now, combine like terms:
(20b - b) + (8 + 2) = 19b + 10
Therefore, the simplified expression is 19b + 10.
2(10b + 4) - (b - 2) = 20b + 8 - (b - 2)
Next, distribute the negative sign inside the parentheses:
20b + 8 - b + 2
Now, combine like terms:
(20b - b) + (8 + 2) = 19b + 10
Therefore, the simplified expression is 19b + 10.
(3g - 4) - 2 (3g + 4)
To simplify the given expression, let's first distribute the number 2 to the terms inside the parentheses:
(3g - 4) - 2(3g + 4)
= 3g - 4 - 2*3g - 2*4
= 3g - 4 - 6g - 8
Now, combine like terms:
= (3g - 6g) + (-4 - 8)
= -3g - 12
Therefore, the simplified expression is -3g - 12.
(3g - 4) - 2(3g + 4)
= 3g - 4 - 2*3g - 2*4
= 3g - 4 - 6g - 8
Now, combine like terms:
= (3g - 6g) + (-4 - 8)
= -3g - 12
Therefore, the simplified expression is -3g - 12.
1/2(x + 4) + 1/4 (4x - 2)
To simplify the given expression, let's first distribute the fractions:
1/2(x + 4) + 1/4 (4x - 2)
= (1/2)x + (1/2)(4) + (1/4)4x - (1/4)2
= (1/2)x + 2/2 + (4/4)x - 1/2
= (1/2)x + 1 + x - 1/2
Next, combine like terms:
= (1/2 + 1)x + (1 - 1/2)
= (3/2)x + 1/2
Therefore, the simplified expression is (3/2)x + 1/2.
1/2(x + 4) + 1/4 (4x - 2)
= (1/2)x + (1/2)(4) + (1/4)4x - (1/4)2
= (1/2)x + 2/2 + (4/4)x - 1/2
= (1/2)x + 1 + x - 1/2
Next, combine like terms:
= (1/2 + 1)x + (1 - 1/2)
= (3/2)x + 1/2
Therefore, the simplified expression is (3/2)x + 1/2.